Book Review: "Financial Therapy: 5 Steps Toward Financial Freedom - Megan McCoy; D. Bruce Ross (Journal of Financial Therapy, 2013)
Financial Therapy: 5 Steps Toward Financial Freedom and its accompanying workbook, Guide to Financial Therapy Forms and Handouts: 5 Steps Toward Financial Freedom, was created to provide an intervention model to help clients become more financially literate and protect them from financial predators.
Keywords: financial therapy; social work